2023
DOI: 10.2174/1871520623666230529141544
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Mechanisms of Molecules Secreted by Trypanosoma cruzi in Colon and Breast Cancer: A Review

Soheil Sadr,
Shakila Ghiassi,
Narges Lotfalizadeh
et al.

Abstract: Background: Molecules secreted by Trypanosoma cruzi (T. cruzi) have beneficial effects on the immune system and can fight against cancer by inhibiting the growth of tumor cells, preventing angiogenesis, and promoting immune activation. Objective: This study aimed to investigate the effects of molecules secreted by Trypanosoma cruzi on the growth of colon and breast cancer cells, to understand the underlying mechanisms of action. Results: Calreticulin from T. cruzi, a 45 kDa protein, participates in essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…11,12 Employing pathogenic microorganisms in cancer immunotherapy is not new. Serratia spp, 13 Streptococcus spp, 14 Listeria monocytogenes, 15 Escherichia coli, 16 Lactobacillus casei, 17 Oncolytic virus, 18 Talimogene laherparepve, 19 Newcastle disease virus, 20 yellow fever vaccine 17D, 21 Trypanosoma cruzi, 22 Echinococcus granulosus, 23,24 and Trichinella spiralis, 25 have been shown to eradicate tumor cells. 26 Toxoplasma gondii (T. gondii) can regulate innate immune cells by invading myeloid cells, typically producing powerful Th1 immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Employing pathogenic microorganisms in cancer immunotherapy is not new. Serratia spp, 13 Streptococcus spp, 14 Listeria monocytogenes, 15 Escherichia coli, 16 Lactobacillus casei, 17 Oncolytic virus, 18 Talimogene laherparepve, 19 Newcastle disease virus, 20 yellow fever vaccine 17D, 21 Trypanosoma cruzi, 22 Echinococcus granulosus, 23,24 and Trichinella spiralis, 25 have been shown to eradicate tumor cells. 26 Toxoplasma gondii (T. gondii) can regulate innate immune cells by invading myeloid cells, typically producing powerful Th1 immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, immunotherapy has played an important role in cancer treatment, standing as the fourth treatment pathway following surgery, chemotherapy, and radiotherapy as the fourth major treatment pathway 3 . In-vitro experiments have shown that certain parasites, including the protozoans Toxoplasma gondii, Trypanosoma cruzi, and the helminths Trichinella spiralis and Echinococcus granulosus represent anti-cancer activities [4][5][6][7] . Nanovaccines are a promising strategy due to their increased lowest immunotoxicity, antigen stability, flexibility of the physical characteristics of nanomaterials, and sustained release.…”
Section: Introductionmentioning
confidence: 99%
“…Despite traditional therapies such as surgery, radiation, and chemotherapy, cancer recurrence remains challenging due to cancer stem cells' self-renewal characteristics 2 . Various strategies for cancer therapy have been trending, like immunotherapy with parasites, such as Trypanosoma cruzi, Trichinella spiralis, and Echinococcus granulosus; however, they need more experimental studies for finding the exact mechanism behind [3][4][5][6] . Even after chemotherapy, a small population of cancer stem cells (CSCs) remains within the tumor.…”
Section: Introductionmentioning
confidence: 99%